(untitled) (PERENNIAL, 2025)
The Lekopancing River, located in Maros Regency, is a crucial source of clean water supply for the people of Makassar City and the surrounding wereas. This study aims to analyze the diversity and role of insects as bioindicators of water quality based on aquatic insect families. The study was conducted in the upstream, middle, and downstream parts of the Lekopancing River, using handpicking and kick sampling for data collection. The collected aquatic insect samples were then identified and analyzed using the diversity index Shannon-Wienner (H’) and Hilsenhoff Family Biotic Index (HFBI) methods, which were widely accepted in ecological research for assessing biodiversity and water quality. The number of aquatic insects found was 614 individuals, consisting of 13 species, 13 families, and 7 orders. The diversity index of aerial insects in the upstream and middle parts of the Lekopancing River was 1.26 and 1.72, while in the downstream part, it was 0.42. The HFBI value of 3.26 in the upstream section is still very good; in the middle section, the HFBI value of 4.84 is considered good; in the downstream section, the HFBI value of 7.00 indicates poor quality.